STUDENT’S PERCEPTION ABOUT ONLINE PROGRAMS - Losada, Analía Verónica (2017)
This article proposes a discussion about how undergraduate students in face-to-face education are perceiving online education by making a brief profile of these students. The research is based on an exploratory case study developed with 129 undergraduate students from six undergraduate programs in Journalism, Pedagogy, Law, Architecture, Electrical Engineering and Civil Engineering at the Tocantins Federal University in Palmas-TO. The methodology was developed through the application and analysis of a questionnaire to the 129 students. Results show that students perception is mostly negative, specially their perceptions regarding academic rigor, fraud and plagiarism.